Analisis Demokratisasi Desa Era Reformasi (Studi Kasus: Desa Tanah Datar, Kalimantan Timur) - Azura, Athalia; Fitriah, Maulidah; Nursadiyah, Nekha Fatimah; Ariesty, Shelma Mutia; Nandari, Tarissa; Fatkhuri, Fatkhuri (Indonesian Journal Publisher, 2024)
This paper aims to examine the implementation of village democratization in the reform era, especially in Tanah Datar Village, East Kalimantan. The author uses a descriptive qualitative research method by collecting data and information using library research. The main source for this scientific writing is the official website of Tanah Datar Village. Meanwhile, the object of this research is the extent to which democratization has progressed in Tanah Datar Village, East Kalimantan. So it can be said that in this research, the author sees that village democratization in the reform era has experienced changes and improvements. This can be seen in the policy-making process involving the community, transparency and government accountability, as is the case in Tanah Datar Village. The implementation of democratization in Tanah Datar Village, East Kalimantan can also be illustrated through the transparency of the use of the APBDes which is described on the village government website. However, there are still several things that can be used as evaluation material for the village government, such as the freedom of association of the Tanah Datar Village community which is still very minimal and the damage which occurs in several village infrastructure. Therefore, it is necessary to evaluate the implementation of democratization in Tanah Datar Village so that the implementation of democratization in the village can run more effectively and be responsive to the various needs of its residents in this reform era.